2021
DOI: 10.3389/fmicb.2021.633881
|View full text |Cite
|
Sign up to set email alerts
|

Seed Biopriming With Trichoderma Strains Isolated From Tree Bark Improves Plant Growth, Antioxidative Defense System in Rice and Enhance Straw Degradation Capacity

Abstract: This study is a unique report of the utilization of Trichoderma strains collected from even tree barks for rice plant growth, its health management, and paddy straw degradation. Seven different spp. of Trichoderma were characterized according to morphological and molecular tools. Two of the isolated strains, namely Trichoderma hebeiensis and Trichoderma erinaceum, outperformed the other strains. Both of the strains controlled four important rice pathogens, i.e., Rhizoctonia solani (100%), Sclerotium oryzae (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 57 publications
4
15
0
1
Order By: Relevance
“…In another study, fourteen endophytes were tested for their efficacy on seed germination in rice and it was found that, Penicillium citrinum showed maximum seed germination, whereas seeds treated with Cladosporium cladosporioides exhibited highest shoot length ( Lalngaihawmi et al., 2018 ). In a recent report, biopriming with Trichoderma strains reduced the mean germination time, increased the seedling vigor and chlorophyll content in two rice varieties ( Swain et al., 2021 ). Therefore, biopriming with endophytes, not only antagonists like Trichoderma , has proven to be a better tool in enhancing the germination in many crops like rice, maize and now in cotton through the findings of this experiment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, fourteen endophytes were tested for their efficacy on seed germination in rice and it was found that, Penicillium citrinum showed maximum seed germination, whereas seeds treated with Cladosporium cladosporioides exhibited highest shoot length ( Lalngaihawmi et al., 2018 ). In a recent report, biopriming with Trichoderma strains reduced the mean germination time, increased the seedling vigor and chlorophyll content in two rice varieties ( Swain et al., 2021 ). Therefore, biopriming with endophytes, not only antagonists like Trichoderma , has proven to be a better tool in enhancing the germination in many crops like rice, maize and now in cotton through the findings of this experiment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, seed biopriming studies are mostly limited to popular biocontrol agents such as Trichoderma viride , T . harzianum and Pseudomonas fluorescens being used for biopriming in many of the crops ( Aamir et al., 2019 ; Ferrigo et al., 2019 ; Singh et al., 2020a ; Swain et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several ACC-deaminase-possessing strains have been found to efficiently enhance stress tolerance of tomato and pepper (Mayak et al, 2004), or wheat (Chandra et al, 2020), under water-deficient conditions (Table 1). The putative priming effect of such strains may be related to enhanced catalase, ascorbate peroxidase or glutathione peroxidase activity in inoculated plants (Mellidou et al, 2021;Swain et al, 2021). By contrast, in some other studies, PGPR inoculation resulted to suppressed expression of stress-responsive genes or genes encoding ROS-scavenging enzymes involved in the protection of plant upon stress application (Goswami and Deka, 2020).…”
Section: Prominent Mechanisms Of Pgpr-mediated Alleviation Of Abiotic...mentioning
confidence: 94%
“…Similarly siderophore, HCN, chitinase and protease production were observed higher on petriplates and vials inoculated with BHU P4 at both room temperature and stressed conditions. Various studies have reported the production of these hydrolytic enzymes by biocontrol agents having crucial role in plant growth promotion and defense mechanism (Aamir et al, 2019;Baiyee et al, 2019;Swain et al, 2021). Siderophore production enhances the uptake of micronutrients such as Fe, Zn, Cu, etc.…”
Section: Screening Of the Trichoderma Isolates On The Basis Of Their In-vitro Plant Growth Promoting And Enzymatic Activitiesmentioning
confidence: 99%